Lycenchelys callista Anderson 1995 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Lycenchelys callista Anderson, 1995. To 20.3 cm (8 in) TL. Central Oregon (44°24’N, 125°07’W) to Tanner Basin, southern California. Benthic; depth: 1,200 –1,830 m (3,937 –6,004 ft). All in Anderson (1995). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 180, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...